PEMANFAATAN MEDIA GAMBAR UNTUK MENINGKATKAN KEMAMPUAN MENGGAMBAR KALIGRAFI LATIN KELAS XI SMA - SUCHI HARTIKA B, Drs. Abd. hafiz, M.Pd, Drs. Ajusril S (Serupa The Journal of Art Education, 2013)
The purpose of this study is to describe the use of picture as learning media to improve drawing ability of Latin calligraphy of elevent grade students. The source of this study is on going precess of learning and it’s result test. Data collected by using the method of observation, recording, and fiel assignment. Research findings there is an increasing of students ability. In the pre test cycle, there are only six students of 32 students, that past the test. After the first cycle done, there is an increasing number of students who past the test, that is 15 of 32 students. Research is continuing on the second cycle with an increasing number of students who passed the test 32 of 32 students. Keywords: picture, Learning Media, Calligraphy